2015
DOI: 10.1080/13691058.2015.1027738
|View full text |Cite
|
Sign up to set email alerts
|

Sexually explicit racialised media targeting men who have sex with men online: a content analysis of high-risk behaviour depicted in online advertisements

Abstract: Sexually explicit media may perpetuate racial and sexual norms among men who have sex with men. While men may be exposed to sexually explicit media in the online settings where they seek sex with other men, no studies to our knowledge have explored the relationship between the racial and sexual content of advertisements appearing in these spaces. In 2011, 217 sexually explicit advertisements on a male sex-seeking website were coded for themes, actor characteristics, and sexual acts depicted using a detailed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
(89 reference statements)
0
7
0
1
Order By: Relevance
“…Evidence for the sexual stereotypes associated with Black MSM has emerged in the context of race-based comparisons among MSM: Both Black men and men of other races characterize Black male partners as physically dominant, aggressive, hypermasculine, and possessing large penises, and Black MSM report subjection to corresponding racial fetishes surrounding their bodies and behaviors (Husbands et al, 2013; Ro, Ayala, Paul, & Choi, 2013; Teunis, 2007; Wilson et al, 2009). The online sexual marketplace reinforces these stereotypes, with hypermasculine or “thug”-like representations of Black men featuring prominently among MSM-targeted sexually explicit advertisements (White, Dunham, Rowley, Reisner, & Mimiaga, 2015). This dominance, aggression, and sexual prowess associated with Black MSM emulate long-established stereotypes of Black men in general (Collins, 2005).…”
Section: Sexual Stereotypes Of Black Msmmentioning
confidence: 99%
“…Evidence for the sexual stereotypes associated with Black MSM has emerged in the context of race-based comparisons among MSM: Both Black men and men of other races characterize Black male partners as physically dominant, aggressive, hypermasculine, and possessing large penises, and Black MSM report subjection to corresponding racial fetishes surrounding their bodies and behaviors (Husbands et al, 2013; Ro, Ayala, Paul, & Choi, 2013; Teunis, 2007; Wilson et al, 2009). The online sexual marketplace reinforces these stereotypes, with hypermasculine or “thug”-like representations of Black men featuring prominently among MSM-targeted sexually explicit advertisements (White, Dunham, Rowley, Reisner, & Mimiaga, 2015). This dominance, aggression, and sexual prowess associated with Black MSM emulate long-established stereotypes of Black men in general (Collins, 2005).…”
Section: Sexual Stereotypes Of Black Msmmentioning
confidence: 99%
“…It is possible that cultural factors are relevant to this association given that differences in SEM use have been shown for other racial/ethnic minority populations. For example, research has documented racialized advertising on adult websites, as well as specific SEM content preferences among Black GBMSM (Nelson, Eaton, & Gamarel, 2016; White, Dunham, Rowley, Reisner, & Mimiaga, 2015). Similar research examining cultural beliefs that may influence SEM exposure and use among Latino GBMSM is needed to better understand the association found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Black/African American MSM in SEM have an economic incentive to participate in the portrayed sexual behaviors and are often depicted as either longing to be submissive/dominated, or presented as men to be feared as a result of their ability to emasculate their partners through physical domination (Kendall, 2004). The portrayed power dynamics (Kendall, 2004) and decreased likelihood of condom use (White et al, 2015) in SEM featuring Black/African American MSM may serve to both trigger and reinforce a preference for condomless sex in SEM.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the images portrayed in SEM may serve to perpetuate racial and sexual norms among MSM. A content analysis of 217 sexually explicit advertisements on a men-seeking-men website found that half (51%) of the ads featured Black/African American men and that ads featuring Black/African American men had an increased odds of portraying condomless sex (White, Dunham, Rowley, Reisner, & Mimiaga, 2015). The authors concluded that the frequent depictions of Black/African American MSM engaging in sexual risk behaviors in SEM may serve to normalize condomless sex, reinforce low peer norms around condom use, and facilitate HIV risk-taking among Black/African American MSM (White et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation